KEPENTINGAN INDONESIA DALAM MELAKUKANIMPOR BUAH APEL DARI TIONGKOK TAHUN 2010-2014 - Aswandi, Laura Nofrika; Pahlawan, Indra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This paper is a bilateral trade study that provides an explain of the Cooperation of two countries. This research discusses about ““Indonesia’s Interest in Importing of Apple in 2010-2014”. The purpose of this research is to know why Indonesia to Cooperate with Tingkok in import of apple. Import of apple is one of the causes of trade deficit between Indonesia and Tiongkok. Tiongkok is the biggest apple producer in the world and Indonesia is one of the country importing apples from Tiongkok.This is qualitative research which used descriptive explanative methods, and collecting datas from books, journals, articles, mass media, official ublications and relevant websites. This paper used the liberalism perspective written by David Ricardo and Adam Smith, analysis unit nation-state and this paper uses theory of International Trade, in this case the theory of comparative advantage by David Ricardo because there is competition between local apple and imported apple, so it takes a significant Indonesian government policy in the process of buying and selling Chinese orange fruit and fruits Local oranges.The result of this research is that Indonesia imports apple from Tiongkok because the productivity of local apple is less in fulfilling domestic consumption and Tiongkok is the biggest Importer country for Indonesia. Also influenced by the composition of imported apples , apple marketing and imported apple prices that are cheaper than local apples.Keywords: Import duty, International Cooperate, Interest, Liberalism perspective.